Association between In-scanner Head Motion with Cerebral White Matter Microstructure: A Multiband Diffusion-weighted MRI study - Kong, Xiang-zhen (PeerJ PrePrints, 2014)
Diffusion-weighted MRI (DW-MRI) has emerged as a promising neuroimaging technique used to depict the biological microstructural properties of the human brain white matter. However, like any other MRI technique, DW-MRI remains subject to head motion during scanning. The association between motion and diffusion metrics is rarely understood. Previous studies have indicated that there are some regions showing significant relationship with diffusion metrics from traditional DW-MRI data with relative few gradient directions (e.g., 30 directions). As imaging techniques improves, additional gradient directions can be acquired in the same scan duration without a significant loss in spatial resolution. The current study examined the association between motion and diffusion metrics with the standard pipeline, tract-based spatial statistics (TBSS), with a multiband diffusion data (i.e., 137 directions). The diffusion metrics used in this study not only the included the commonly used metrics (i.e., FA and MD) in DW-MRI studies, but also a newly proposed inter-voxel metric, local diffusion homogeneity (LDH). The positive association was observed with MD, while the negative association with LDH. No significant association between motion and FA was observed. These results indicate that there is a similar link between motion and diffusion metrics in the multiband diffusion data. Finally, the motion-diffusion association is discussed.
Keywords: White Matter; Head Motion; Microstructure; Diffusion MRI